Pengaruh CAR, FDR, Dan BOPO Terhadap ROA Pada Bank Syariah Di Indonesia - Yuliana, Intan Rika; Listari, Sinta (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
Banking companies, including Islamic banking, need to avoid problems that can cause financial failure, which can make the bank unable to carry out its business operations and may end up in bankruptcy, so that the level of soundness of the bank based on risk must always be monitored. Therefore, banks must maintain their financial ratios in accordance with Bank Indonesia decisions and maintain their performance. So analyzing the effect of the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and the Ratio of Operating Costs to Operating Income (BOPO) on Return On Assets (ROA) in Islamic Banks is considered very important. This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operational Costs on Operating Income (BOPO) on Return On Assets (ROA) at Islamic Commercial Banks in Indonesia. This research includes quantitative research and the type of data used is secondary data. The data used in this study is the ratio of CAR, FDR, BOPO, and ROA for the period 2014–2019 which was obtained from the annual Financial Statements on the official website of each bank. The population in this study were 14 Islamic Commercial Banks in Indonesia. After passing the purposive sampling stage, there were 6 samples of Sharia Commercial Banks that were suitable for use, namely BCA Syariah, BNI Syariah, Bank Mega Syariah, Bank Muamalat Indonesia, Bank Panin Dubai Syariah and BRI Syariah. The analytical method used in this research is Multiple Linear Regression Analysis. The results of the partial study with the t-test showed that the CAR and FDR variables had a positive and significant effect on the ROA of Islamic commercial banks. While the BOPO variable has a negative and significant effect on the ROA of Islamic commercial banks. And the results of the f test show that the CAR, FDR, and BOPO variables together have a significant influence on the ROA of Islamic commercial banks. The predictive ability of these three variables on ROA is 82.7%, the remaining 17.3% is explained by other variables outside of this research. Keywords: Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operating Expenses per Operating Income (BOPO), Return On Assets (ROA)